â€œThe Relationship between Product Quality and Customer Satisfaction and the Impact on Customer Loyalty (An Empirical Study of iPhone in Pontianakâ€ - B12111020, Marlisa (Jurnal Manajemen Update, 2015)
Today’s competition in smartphones industries is getting tougher, this tighter competition is mainly caused by the increasing numbers of smartphones brands in the industry (either old or new players), increasing level of smartphones user’s knowledge, and also due to the easiness in gaining information. It encourages the company to create and provide innovative products with the highest quality so they are able to fulfill customer’s expectations.Meeting the customer’s expectations is a dream of every company and the only way to satisfy and get loyal customers. Just like what have been described above, the main thing that should be given as priority in the conditions of intense is customer satisfaction, so the company can compete, survive, gain profits, and finally reach the biggest dream of every company which is loyal customers. This study aims to determine the direct and indirect influences of product quality on customer satisfaction and customer loyalty. The research method used in this research is quantitative research methods, with 100 of iPhone users in Pontianak as the respondents. Data was collected by interviewing respondents and spreading the questionnaires. The data was analyzed with path analysis method.The result shows that product quality has influences both on customer satisfaction and customer loyalty. And this research also had shown if there is a positive and significant influence of customer satisfaction on customer loyalty. Apple Company was suggested to be aware in improving and keeping iPhone’s product quality in order to get the higher level of customer satisfaction and also to get more loyal customers in Pontianak. Besides, it was also suggested by the author for Apple Company to give more attention on the other variables which were not included in this research such as; brand image, customer value, and corporate image. Keywords: Product Quality, Customer Satisfaction, Customer Loyalty, iPhone.